Improving Agricultural Productivity and Markets : The Role of Information and Communication Technologies - McNamara, Kerry (World Bank, Washington, DC, 2012)
Raising the productivity of smallholders is a necessary condition for increasing incomes and improving livelihoods among the rural poor in most developing countries. This increased productivity is essential to both household food security and to agriculture-based growth and poverty reduction in the larger economy. Smallholder productivity is limited by a variety of constraints including poor soils, unpredictable rainfall, and imperfect markets, as well as lack of access to productive resources, financial services, or infrastructure. Information and communication technologies (ICT) are also vitally important to commercial and large-scale agriculture, and to agriculture-related services and infrastructure such as weather monitoring and irrigation. This note focuses on the sometimes less-obvious importance of ICT in improving the information, communication, transaction, and networking elements of smallholder agriculture in developing countries.